Reasons and Factors Contributing to Chinese Patients’ Preference for Ustekinumab in Crohn’s Disease: A Multicenter Cross-Sectional Study - Yao, Lingya; Zhu, Xiao; Shao, Bule; Liu, Rongbei; Li, Zhilun; Wu, Lexi; Chen, Jin; Cao, Qian (Frontiers in Pharmacology, 2021)
Background and Aims: Ustekinumab (UST) was approved in China for treating moderate to severe Crohn’s disease (CD) in 2020. We aimed to identify the reasons and possible contributing factors for UST preference in Chinese patients with CD. Methods: We conducted a multicenter cross-sectional survey among patients with moderate to severe CD who underwent UST treatment in 27 hospitals. Patients completed a 46-item questionnaire that included information on demographics, clinical characteristics, reasons in favor of UST and shared decision-making perception. Logistic regression analysis was performed to examine the predictive factors of different UST preferences. Results: Overall, 127 patients (73 males; mean age, 25.9±9.9 years) completed the questionnaire. Most patients (74.8%) had biologic failure. The most common reason for the latest treatment disconnection was unresponsiveness to the previous medications. The major UST information sources were physicians (96.1%). Nearly half of the patients (44.9%) reported shared decision-making regarding UST treatment. No difference was found in the decision-making patterns in terms of sex and age. The most influential reason for UST preference was “effectiveness” (77%, 98/127), followed by “safety” (65%, 83/127), “frequency of administration” (39%, 49/127), and “mode of administration” (37%, 47/127). Multivariate logistic regression analysis revealed that a positive self-rated health status was a contributing factor for UST preference with a low frequency of administration. Conclusions: This is the first multicenter survey of Chinese patients with CD to identify the possible contributing factors for UST preference. Treatment choice should be discussed with patients because individual preferences are determined by diverse factors.